Tff3 Deficiency Protects against Hepatic Fat Accumulation after Prolonged High-Fat Diet - Seselja, Kate; Bazina, Iva; Vrecl, Milka; Welss, Jessica; Schicht, Martin; Mihalj, Martina; Kopacin, Vjekoslav; Paulsen, Friedrich; Pirman, Tatjana; Loncar, Mirela Baus (Life, 2022)
Trefoil factor 3 (Tff3) protein is a small secretory protein expressed on various mucosal surfaces and is involved in proper mucosal function and recovery via various mechanisms, including immune response. However, Tff3 is also found in the bloodstream and in various other tissues, including the liver. Its complete attenuation was observed as the most prominent event in the early phase of diabetes in the polygenic Tally Ho mouse model of diabesity. Since then, its role in metabolic processes has emerged. To elucidate the complex role of Tff3, we used a new Tff3-deficient mouse model without additional metabolically relevant mutations (Tff3-/-/C57BL/6NCrl) and exposed it to a high-fat diet (HFD) for a prolonged period (8 months). The effect was observed in male and female mice compared to wild-type (WT) counter groups (n = 10 animals per group). We monitored the animals' general metabolic parameters, liver morphology, ultrastructure and molecular genes in relevant lipid and inflammatory pathways. Tff3-deficient male mice had reduced body weight and better glucose utilization after 17 weeks of HFD, but longer HFD exposure (32 weeks) resulted in no such change. We found a strong reduction in lipid accumulation in male Tff3-/-/C57BL/6NCrl mice and a less prominent reduction in female mice. This was associated with downregulated peroxisome proliferator-activated receptor gamma (Ppar gamma) and upregulated interleukin-6 (Il-6) gene expression, although protein level difference did not reach statistical significance due to higher individual variations. Tff3-/-/C57Bl6N mice of both sex had reduced liver steatosis, without major fatty acid content perturbations. Our research shows that Tff3 protein is clearly involved in complex metabolic pathways. Tff3 deficiency in C57Bl6N genetic background caused reduced lipid accumulation in the liver; further research is needed to elucidate its precise role in metabolism-related events.
CRIS-Team WoS Importer:2022-09-09